Tumor Akkermansia muciniphila predicts clinical response to immune checkpoint inhibitors in non-small-cell lung cancer patients with low PD-L1 expression - Shimizu, Takashi; Ohkuma, Ryotaro; Homma, Mayumi; Nakayama, Shingo; Sasaki, Yosuke; Muto, Satoshi; Ieguchi, Katsuaki; Watanabe, Makoto; Taguchi, Akashi; Takayanagi, Daisuke; Wada, Youichiro; Horiike, Atsushi; et al. (Frontiers in Immunology, 2025)
IntroductionA prior retrospective analysis demonstrated that quantifying Programmed Cell Death Ligand 1 (PD-L1) expression using a phosphor-integrated dot (PID) score effectively predicted immune checkpoint inhibitor (ICI) efficacy in non-small-cell lung cancer (NSCLC) and other cancers. However, PD-L1 expression proved unreliable in some patients with low PD-L1 levels, highlighting the need for alternative biomarkers. A previous cohort study in NSCLC patients linked intestinal Akkermansia muciniphila (Akk) presence to improved ICI efficacy, particularly in low PD-L1 subgroups. Here, we evaluated tumor tissue Akk expression via immunohistochemical staining as a potential biomarker for ICI response in NSCLC.MethodsWe retrospectively analyzed tumor tissues from 60 metastatic or recurrent NSCLC patients treated with ICIs. Immunohistochemical (IHC) staining was performed to assess Akk and PD-L1 expression, along with CD3 and CD68 in PD-L1-low samples. Transcriptomic profiling using RNA-sequencing was conducted on tumor samples to identify Akk-related gene expression patterns.ResultsTumor Akk expression showed no correlation with PD-L1 levels assessed via PID. Survival and multivariable Cox regression analyses revealed no association between Akk expression and progression-free survival (PFS) or overall survival (OS). In high PD-L1 patients, Akk status did not influence outcomes. However, among low PD-L1 patients, Akk-positive cases exhibited significantly worse PFS compared to Akk-negative cases (OS remained unchanged). Transcriptome analysis indicated that Akk positivity in low PD-L1 samples exhibited enrichment in oxidative phosphorylation and amyotrophic lateral sclerosis-related pathways and downregulation of spliceosome-associated pathways. No significant differences in tumor-infiltrating CD3+ T cells or CD68+ macrophages were observed between Akk-positive and Akk-negative tumors in the PD-L1-low groupConclusionsTumor-associated Akk may serve as a negative predictive biomarker for ICI efficacy in NSCLC patients with low PD-L1 expression. Our findings suggest that tumor microbiota profiling, particularly targeting Akk, could refine patient stratification and therapeutic decision-making.